The Effect Of Deep Breath Relaxation and Isometric Handgrip Exercise On Reducing Blood Pressure In Older Adults With Hypertension - Anggraini, Yuyun; Andhini, Dhona; Muharyani, Putri Widita (Jurnal Keperawatan Universitas Jambi, 2025)
Intorduction : Hypertension is a major risk factor for death from cardiovascular disease.In addition to pharmacological therapy, companion therapy is also needed that aims to reduce blood pressure, including physical activity therapy and relaxation therapy. Isometric handgrip exercises and relaxation therapy can activate immediate impulses by increasing muscle tension and relaxing the body so that a blood pressure response can occur. This study aims to determine the effect of a combination of isometric han dgrip exercise therapy and deep breathing relaxation on blood pressure in elderly people with hypertension. Methods : This research is a pre-experimental quantitative research with a one group pretest posttest design. The intervention consisted of isometric grip exercises and deep breathing relaxation for 20 minutes. The sample for this research consisted of 17 respondents using purposive sampling. Statistical analysis of this research uses a paired t test with a value of α = 0.05. Results : The results of p value = 0.000 (α ≤0.05) which means that there is a significant effect of a combination of isometric handgrip exercise therapy and deep breathing relaxation on reducing blood pressure in elderly people with hypertension Conclusion : The results of the research show that the combination of isometric handgrip exercise therapy and deep breathing relaxation can significantly reduce bl  ood pressure in elderly people with hypertension. The combination of isometric handgrip exercise therapy and deep breathing relaxation can be recommended as a treatment to complement pharmacological therapy in reducing blood pressure.tructions for authors.